2001
DOI: 10.1111/j.1471-0528.2001.00116.x
|View full text |Cite
|
Sign up to set email alerts
|

Screening with a uterine Doppler in low risk pregnant women followed by low dose aspirin in women with abnormal results: a multicenter randomised controlled trial

Abstract: Collaborators and participating centres of the French Doppler study group are listed on page 517.Objectives To assess whether systematic screening with an uterine artery Doppler in low risk pregnant women followed by the prescription of low dose aspirin in cases with abnormal results reduced the incidence of intrauterine growth restriction and pre-eclampsia.Design A multicentre randomised trial.Population 3317 low risk pregnant women. In the Doppler group, the uterine artery Doppler was performed between 20 an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
32
1
1

Year Published

2004
2004
2019
2019

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 30 publications
(36 citation statements)
references
References 26 publications
1
32
1
1
Order By: Relevance
“…112,113 These findings could be explained by either the low predictive accuracy of Doppler ultrasonography or by the modest efficacy of aspirin to prevent preeclampsia.…”
Section: Discussionmentioning
confidence: 93%
“…112,113 These findings could be explained by either the low predictive accuracy of Doppler ultrasonography or by the modest efficacy of aspirin to prevent preeclampsia.…”
Section: Discussionmentioning
confidence: 93%
“…Large multi-centre studies evaluated whether aspirin treatment, started at 22-24 weeks of gestation, would be beneficial in women with abnormal midtrimester uterine artery Doppler results (Yu et al, 2003;Goffinet et al, 2001;Subtil et al, 2003). With respect to pre-eclampsia, no alteration in pregnancy outcome was observed following aspirin intake.…”
Section: Discussionmentioning
confidence: 96%
“…Assessed during midtrimester, such abnormal Doppler findings indicate a substantially increased risk for developing pre-eclampsia (Conde-Agudelo et Chien et al, 2000). In randomized controlled trials using aspirin treatment for preventing pre-eclampsia in women with abnormal midtrimester uterine artery Doppler results, Doppler screening for predicting pre-eclampsia yielded sensitvities up to 60% and positive predictive values up to 40% (Yu et al, 2003;Goffinet et al, 2001;Subtil et al, 2003). However, in women with abnormal midtrimester Doppler measurements, Aspirin treatment did not alter the pregnancy outcome compared to controls.…”
Section: Combination Of Biochemical Markers With Uterine Artery Dopplmentioning
confidence: 98%
“…Seventy‐two reports from 68 trials met the inclusion criteria and were included in the systematic review (Figure ). Forty‐four trials reported on potential interventions for the prevention of FGR and 24 (29 studies) reported on interventions for the treatment of pregnancies affected by FGR. Five papers reporting outcomes from the DIGITAT trial and two from the TRUFFLE trial were included.…”
Section: Resultsmentioning
confidence: 99%